Introducing Indonesia's Traditional Pecah Piring Sport to Nanyang Technological University Students in Singapore: A Community Engagement for Cultural Diplomacy - Muhammad Fahrezi Harahap; Mizar Aulia; Nadhira Yasmine Ahmad; Muhammad Isnandar; Elisa Haddina (Inspire Global Insight Journal, 2026)
Objective: This community service program aimed to increase the knowledge, understanding, and appreciation of students at Nanyang Technological University (NTU), Singapore, toward the Indonesian traditional sport Pecah Piring (Broken Plate) as a medium for character education, cultural preservation, and cultural diplomacy. Methodology: A participatory approach was employed through three stages: preparation, implementation, and evaluation. The implementation included presentations on the history, philosophy, cultural values, and rules of the Pecah Piring game, followed by demonstrations and group-based hands-on practice. Program effectiveness was evaluated using observations, discussions, and participant response questionnaires, while the collected data were analyzed descriptively. Results: The program successfully enhanced participants' understanding and appreciation of Indonesian traditional sports. Evaluation results indicated excellent outcomes, with material understanding reaching 92%, participant engagement 95%, teamwork 94%, appreciation of Indonesian culture 96%, and overall satisfaction 97%. The experiential learning approach effectively promoted active participation while strengthening values of sportsmanship, cooperation, communication, leadership, and cross-cultural understanding. Conclusions: The socialization of the traditional sport Pecah Piring proved to be an effective strategy for promoting Indonesian cultural heritage in an international academic environment. The participatory and experiential learning model not only increased participants' knowledge and cultural appreciation but also demonstrated the potential of traditional sports as a medium for character education, cultural diplomacy, and the internationalization of higher education. Similar programs should be expanded through sustainable international collaborations to strengthen global recognition of Indonesia's cultural heritage.